-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathDivision.agda
227 lines (197 loc) · 7.92 KB
/
Division.agda
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
module Division where
open import Data.Empty using (⊥; ⊥-elim)
open import Data.Fin using (Fin; zero; suc; toℕ)
open import Data.Maybe as M using (Maybe; nothing; just; drop-just)
open import Data.Nat
open import Data.Nat.Properties using (m≤m+n; ≤-step; ≤⇒≤′)
open import Data.Nat.Properties.Simple
using (*-right-zero; *-comm; +-right-identity; +-suc; +-comm)
open import Data.Unit using (⊤; tt)
open import Function
open import Relation.Binary using (module Setoid)
open import Relation.Binary.PropositionalEquality as PEq
using (_≡_; _≢_; refl; sym; trans; subst; cong; module ≡-Reasoning)
open import Relation.Nullary using (Dec; yes; no)
data _divides_ : ℕ → ℕ → Set where
div : {m n : ℕ} (k : ℕ) (eq : n ≡ k * m) → m divides n
-- Basic lemmata about divisibility
zero-divides⇒is-zero : ∀ {n} → zero divides n → n ≡ zero
zero-divides⇒is-zero (div k eq) = trans eq (*-right-zero k)
m-divides-zero : ∀ {m} → m divides zero
m-divides-zero = div zero refl
-- I like proving this separately, and not relying on absurd patterns
suc≢zero : ∀ {n} → suc n ≢ zero
suc≢zero eq = subst P eq tt
where
P : ℕ → Set
P zero = ⊥
P (suc n) = ⊤
-- A helper type for bounded recursive checking of divisors
data divides≤′ : (l m n : ℕ) → Set where
div≤′ : {l m n : ℕ} (k : ℕ) (le : k ≤′ l) (eq : n ≡ k * m) → divides≤′ l m n
dec-lemma : (l m n : ℕ) → Dec (divides≤′ l (suc m) (suc n))
dec-lemma zero m n = no (λ { (div≤′ .0 ≤′-refl eq) → suc≢zero eq })
dec-lemma (suc l) m n with dec-lemma l m n
dec-lemma (suc l) m n | yes (div≤′ k le eq) = yes (div≤′ k (≤′-step le) eq)
dec-lemma (suc l) m n | no ¬d with suc n ≟ suc l * suc m
dec-lemma (suc l) m n | no ¬d | yes eq = yes (div≤′ (suc l) ≤′-refl eq)
dec-lemma (suc l) m n | no ¬d | no ¬eq =
no (λ { (div≤′ _ ≤′-refl eq) → ¬eq eq
; (div≤′ k (≤′-step le) eq) → ¬d (div≤′ k le eq) })
-- The helper type gives us what we want
divides≤′⇒divides : ∀ {l m n} → divides≤′ l m n → m divides n
divides≤′⇒divides (div≤′ k le eq) = div k eq
divides⇒divides≤′ : ∀ {m n} → suc m divides n → divides≤′ n (suc m) n
divides⇒divides≤′ {m} {n} (div k eq) = div≤′ k (≤⇒≤′ (begin
k ≤⟨ m≤m+n k (m * k) ⟩
k + m * k ≡⟨⟩
suc m * k ≡⟨ sym (*-comm k (suc m)) ⟩
k * suc m ≡⟨ sym eq ⟩
n ∎)) eq
where
open ≤-Reasoning renaming (_≈⟨⟩_ to _≡⟨⟩_)
-- Main theorem: divisibility is decidable
_divides?_ : (m n : ℕ) → Dec (m divides n)
zero divides? zero = yes (div zero refl)
zero divides? suc n = no (suc≢zero ∘ zero-divides⇒is-zero)
suc m divides? zero = yes m-divides-zero
suc m divides? suc n with dec-lemma (suc n) m n
suc m divides? suc n | yes p = yes (divides≤′⇒divides p)
suc m divides? suc n | no ¬p = no (¬p ∘ divides⇒divides≤′)
-- Each number is divisible by 1 and itself
one-divides-n : ∀ n → 1 divides n
one-divides-n n = div n (begin
n ≡⟨ sym (+-right-identity n) ⟩
n + 0 ≡⟨ refl ⟩
1 * n ≡⟨ *-comm 1 n ⟩
n * 1 ∎)
where
open ≡-Reasoning
n-divides-n : ∀ n → n divides n
n-divides-n n = div 1 (begin
n ≡⟨ sym (+-right-identity n) ⟩
n + 0 ≡⟨ refl ⟩
1 * n ∎)
where
open ≡-Reasoning
-- Division
≤-minus : ∀ {x y} → x ≤ y → ℕ
≤-minus {y = y} z≤n = y
≤-minus (s≤s x≤y) = ≤-minus x≤y
--_/suc_ : ℕ → ℕ → ℕ
--m /suc n with suc n ≤? m
--m /suc n | yes sucn≤m = {!≤-minus sucn≤m /suc n!}
--m /suc n | no _ = zero
-- The totality checker fails because it can't establish that `≤-minus sucn≤m`
-- is structurally smaller than `m`. We could deduce that `≤-minus sucn≤m` is
-- numerically less than `m`, but we'd still need to do some work to get this
-- into a form the totality checker would be happy with.
-- A representation of natural numbers as a quotient and a remainder
data QuotRem (n : ℕ) : Set where
_*n+_ : (q : ℕ) (r : Fin n) → QuotRem n
-- Opposite of inject₁
tighten : ∀ {n} (x : Fin (suc n)) → toℕ x ≢ n → Fin n
tighten {zero} zero neq = ⊥-elim (neq refl)
tighten {suc n} zero neq = zero
tighten {zero} (suc ()) neq
tighten {suc n} (suc x) neq = suc (tighten x (neq ∘ cong suc))
-- tighten preserves numerical value.
tighten-correct :
∀ {n} (x : Fin (suc n)) (neq : toℕ x ≢ n) → toℕ (tighten x neq) ≡ toℕ x
tighten-correct {zero} zero neq = ⊥-elim (neq refl)
tighten-correct {suc n} zero neq = refl
tighten-correct {zero} (suc ()) neq
tighten-correct {suc n} (suc x) neq =
cong ℕ.suc (tighten-correct x (neq ∘ cong suc))
-- Successor function for Fin n, failing when there is no larger number
sucF : ∀ {n} → Fin n → Maybe (Fin n)
sucF {zero} ()
sucF {suc n} x with toℕ x ≟ n
sucF {suc n} x | yes p = nothing
sucF {suc n} x | no ¬p = just (suc (tighten x ¬p))
-- If sucF returns something, it is one larger than the number it was given
sucF-correct : ∀ {n} (x y : Fin n) → sucF x ≡ just y → suc (toℕ x) ≡ toℕ y
sucF-correct {suc zero} zero y eq = ⊥-elim (subst P eq tt)
where
P : ∀ {a} {A : Set a} → Maybe A → Set
P (just x) = ⊥
P nothing = ⊤
sucF-correct {suc (suc n)} zero y eq =
let eq′ = drop-just (reflexive eq) in
cong toℕ eq′
where open Setoid (M.setoid (PEq.setoid _))
sucF-correct {suc n} (suc x) y eq with suc (toℕ x) ≟ n
sucF-correct {suc n} (suc x) y eq | yes p = ⊥-elim (subst P eq tt)
where
P : ∀ {a} {A : Set a} → Maybe A → Set
P (just x) = ⊥
P nothing = ⊤
sucF-correct {suc n} (suc x) y eq | no ¬p =
let eq′ = drop-just (reflexive eq) in
begin
suc (suc (toℕ x))
≡⟨ cong suc (PEq.sym (tighten-correct (suc x) ¬p)) ⟩
suc (toℕ (tighten (suc x) ¬p))
≡⟨⟩
toℕ (suc (tighten (suc x) ¬p))
≡⟨ cong toℕ eq′ ⟩
toℕ y
∎
where open Setoid (M.setoid (PEq.setoid _))
open ≡-Reasoning
-- Successor function for numbers represented as quotient and remainder
sucQR : ∀ {n} → QuotRem (suc n) → QuotRem (suc n)
sucQR (q *n+ r) with sucF r
sucQR (q *n+ r) | just r′ = q *n+ r′
sucQR (q *n+ r) | nothing = suc q *n+ zero
ℕ→QuotRem : ∀ {n} → ℕ → QuotRem (suc n)
ℕ→QuotRem zero = zero *n+ zero
ℕ→QuotRem (suc m) = sucQR (ℕ→QuotRem m)
QuotRem→ℕ : ∀ {n} → QuotRem n → ℕ
QuotRem→ℕ {n} (q *n+ r) = q * n + toℕ r
-- sucQR gives the representation of the successor of the number represented
-- by its argument.
QuotRem→ℕ-sucQR : ∀ {n} x → QuotRem→ℕ {suc n} (sucQR x) ≡ suc (QuotRem→ℕ x)
QuotRem→ℕ-sucQR {n} (q *n+ r) with toℕ r ≟ n
QuotRem→ℕ-sucQR {n} (q *n+ r) | yes p = cong suc $
begin
n + q * suc n + 0
≡⟨ +-right-identity _ ⟩
n + q * suc n
≡⟨ +-comm n (q * suc n) ⟩
q * suc n + n
≡⟨ cong (λ x → q * suc n + x) (sym p) ⟩
q * suc n + toℕ r
∎
where open ≡-Reasoning
QuotRem→ℕ-sucQR {n} (q *n+ r) | no ¬p =
begin
q * suc n + suc (toℕ (tighten r ¬p))
≡⟨ cong (λ x → q * suc n + suc x) (tighten-correct r ¬p) ⟩
q * suc n + suc (toℕ r)
≡⟨ +-suc (q * suc n) (toℕ r) ⟩
suc (q * suc n + toℕ r)
∎
where open ≡-Reasoning
-- div
_/suc_ : ℕ → ℕ → ℕ
m /suc n with ℕ→QuotRem {n} m
m /suc n | q *n+ r = q
-- mod
_%suc_ : ℕ → ℕ → ℕ
m %suc n with ℕ→QuotRem {n} m
m %suc n | q *n+ r = toℕ r
test : ℕ
test = {!ℕ→QuotRem {3} 13!} -- 13 / 4 = 3 + 1 / 4
-- Inverse in one direction
ℕ→QuotRem→ℕ : ∀ {n} m → QuotRem→ℕ (ℕ→QuotRem {n} m) ≡ m
ℕ→QuotRem→ℕ zero = refl
ℕ→QuotRem→ℕ (suc m) =
begin
QuotRem→ℕ (sucQR (ℕ→QuotRem m))
≡⟨ QuotRem→ℕ-sucQR (ℕ→QuotRem m) ⟩
suc (QuotRem→ℕ (ℕ→QuotRem m))
≡⟨ cong suc (ℕ→QuotRem→ℕ m) ⟩
suc m
∎
where open ≡-Reasoning